PROJECTING ENERGY EFFICIENT BUILDINGS WITH ENVIRONMENTAL REQUIREMENTS - U.I Rustamov (Western European Studies, 2024)
Recently, many designers have increasingly decided to create buildings and structures that are environmentally friendly and energy-efficient. The article discusses some aspects of the design of private houses without the help of architects and designers. Several important rules are proposed with the help of an ordinary pencil and a notebook for designing private eco-friendly houses.
Keywords: cozy housing; own house; checkered notebook; contour